PENGARUH STRES KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA PELAYANAN TEKNIK DI PT. MAHIZA KARYA MANDIRI CABANG BEKASI - Edward Efendi Silalahi,; Annisa Dianti, (Juremi: Jurnal Riset Ekonomi, 2022)
PT Mahiza Karya Mandiri is a service company for engineering and electrical disturbances. Research identification shows that there are indications of fluctuating employee job satisfaction in the company, so it is necessary to identify the factors that can affect employee job satisfaction. Factors that affect employee job satisfaction identified from this study include job stress and work motivation. The purpose of this study is to determine the effect of work stress and work motivation on employee job satisfaction in technical services at PT. Mahiza Karya Mandiri Cabang Bekasi. This research is a quantitative research using the saturated sampling method on the employees of the Engineering Services section at PT. Mahiza Karya Mandiri Cabang Bekasi. The source of this research data is primary data in the form of questionnaires or questionnaires that have been distributed to 75 respondents. Data processing using SPSS Version 25 analysis technique. The analytical method used is the Multiple Linear Regression method. The results of this study indicate that the variables of work stress and work motivation simultaneously have a positive and significant effect on employee job satisfaction. Furthermore, in the partial test of the work stress variable, the t-count value of 3.743 is greater than the t-table value of 1.993 and the work motivation variable with the tcount of 8.005 is greater than the t-table value of 1.993